2020
DOI: 10.1159/000508349
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Position on Lung Deposition of Nebulized Surfactant in Newborn Piglets on Nasal Continuous Positive Airway Pressure

Abstract: <b><i>Introduction:</i></b> The ideal body position during surfactant nebulization is not known. <b><i>Objective:</i></b> The aim of this study was to determine whether body positioning during surfactant nebulization influences surfactant distribution and deposition in the lungs. <b><i>Methods:</i></b> Twenty-four 12- to 36-h-old full-term<b><i></i></b>piglets (1.3–2.2 kg) on nasal continuous positive airway pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…However, animal 1 was positioned with the right side up and animal 2 with the left side up. Interestingly, even though total lung deposition was 38.6% and 47.8% in animal 1 and 2, respectively, surfactant deposition in the dependent lungs accounted for 33.4% and 43.7% in each case, suggesting the formation of a surfactant film within the airways after nebulization which distributes preferentially to the dependent lung [122,130]. Nevertheless, animal 2 and animal 4 were both positioned with the left side up but the difference in lung deposition was evident: total lung deposition in animal 4 was just 3.3%, whereas deposition in the nasopharynx (18.4%) and stomach (20.6%) accounted for 39% of the nominal surfactant dose.…”
Section: Table 4 Comparison Of the Parameters Required By Compendial mentioning
confidence: 97%
See 3 more Smart Citations
“…However, animal 1 was positioned with the right side up and animal 2 with the left side up. Interestingly, even though total lung deposition was 38.6% and 47.8% in animal 1 and 2, respectively, surfactant deposition in the dependent lungs accounted for 33.4% and 43.7% in each case, suggesting the formation of a surfactant film within the airways after nebulization which distributes preferentially to the dependent lung [122,130]. Nevertheless, animal 2 and animal 4 were both positioned with the left side up but the difference in lung deposition was evident: total lung deposition in animal 4 was just 3.3%, whereas deposition in the nasopharynx (18.4%) and stomach (20.6%) accounted for 39% of the nominal surfactant dose.…”
Section: Table 4 Comparison Of the Parameters Required By Compendial mentioning
confidence: 97%
“…However, position changes alter the upper respiratory tract angles and may therefore influence the fate of a nebulized drug. A recent scintigraphy study by Cunha-Goncalves et al in newborn piglets ventilated with nCPAP investigated the impact of body positioning on the lung distribution of nebulized surfactant [130]. In this study, all animals received 200 mg/kg of nebulized, radiolabelled surfactant using a customized eFlow Neos vibrating-membrane nebulizer placed between the Y piece and the nCPAP interface (customized nasal prongs).…”
Section: Miscellaneousmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies on piglets showed mean lung phospholipids of 100 mg/kg was achieved with higher dosages of nebulized surfactant, 41,42 that mean lung deposition was significantly higher when nebulization was performed in the prone position 43 and that lung deposition was significant irrespective of the type of noninvasive respiratory support used during nebulized SRT 44 …”
Section: Aerosolizationmentioning
confidence: 99%